The potential use of Endostatin and Angiopoietin-2 as valuable biomarkers for the prediction of Diabetic Nephropathy in Type 2 Diabetes Mellitus - Mohamed Salem; Alaliaa Sallam; Eman Amer; Hala O. El-Mesallamy (Ain Shams University, 2019)
Diabetic Nephropathy (DN) is considered a serious capillary complication of diabetes mellitus (DM) which leads to end-stage renal disease. Endostatin (EST) is considered as collagen XVIII fragment formed during extracellular matrix remodeling (ECMR). EST acts as an anti-angiogenic factor. Angiopoietin-2 (Ang II) is a growth factor that increases in several conditions, such as hyperglycemia. The present study was to scrutinize the association of EST and Ang II serum levels with nephropathy in patients with type 2 diabetes mellitus (T2DM). A total of 30 healthy individuals (control) and 120 T2DM patients classified into 60 patients with microalbuminuria and 60 patients without microalbuminuria), aged 45-65 years were included. Fasting Plasma Glucose (FPG), HbA1C%, lipid profile, urinary albumin/creatinine ratio of 30-300 mg/g (UACR), serum urea and creatinine levels were assessed. Both EST and Ang II were measured using the ELISA technique. Ang II and EST levels were elevated in patients with T2DM groups compared with the healthy control group (P<0.001). EST and Ang II were significantly correlated to UACR (r= 0.753, P<0.001) (r= 0.685, P<0.001) and therefore indicate progress to DN. Circulating EST and Ang II were significantly associated with T2DM and predict progression of DN and therefore can be used as biomarkers for the prediction of DN in such a group of patients.